2013
DOI: 10.1158/0008-5472.can-12-2072
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Cancer Therapy with a 2-Deoxyglucose–Based Adriamycin Complex

Abstract: Adriamycin (ADM) has been effective against many types of solid tumors in clinical applications. However, its use is limited because of systemic toxicities, primarily cardiotoxicity, and multidrug resistance. In this study, a new active receptor-mediated complex, ADM conjugated with 2-amino-2-deoxy-D-glucose and succinic acid (2DG-SUC-ADM), was designed to target tumor cells through glucose transporter 1 (GLUT1). MTT assay and confocal images showed that the complex had better inhibition rate to tumor cells an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 37 publications
3
64
0
2
Order By: Relevance
“…The present observation, therefore, support the above mentioned studies from the treatment time point of view. In addition, it was shown that 2DG could significantly enhanced anticancer activity of doxorubicin and decrease organ toxicity and enhance the antitumor efficacy (Cao et al, 2013). The present data, therefore, strongly suggest that further preclinical studies should be undertaken to investigate the mechanisms of action as well as potential of glycolytic inhibitorsincluding 2DG to selectively modulate the radiation response of treatment tumors, including malignant radioresistance tumors.…”
Section: Discussionmentioning
confidence: 58%
“…The present observation, therefore, support the above mentioned studies from the treatment time point of view. In addition, it was shown that 2DG could significantly enhanced anticancer activity of doxorubicin and decrease organ toxicity and enhance the antitumor efficacy (Cao et al, 2013). The present data, therefore, strongly suggest that further preclinical studies should be undertaken to investigate the mechanisms of action as well as potential of glycolytic inhibitorsincluding 2DG to selectively modulate the radiation response of treatment tumors, including malignant radioresistance tumors.…”
Section: Discussionmentioning
confidence: 58%
“…After treatment, the mice were euthanized, the organs and tumors were collected and fixed in 10% neutral buffered formalin, embedded in paraffin blocks for H&E staining, and visualized using an optical microscope. To investigate drug distribution, histological sections were analyzed using CLSM 51.…”
Section: Methodsmentioning
confidence: 99%
“…A 2013 report by Gu and coworkers presented the synthesis and cell culture and in vivo evaluation of a 2-amino-2-deoxyglucose conjugate of the topoisomeriase II inhibitor adriamycin (doxorubicin), linked using a succinic acid spacer (Figure 8g) [69]. This adriamycin glycoconjugate was designed to enhance the selectivity of adriamycin to cancer cells, and thus to counteract the dose-limiting toxicity of adriamycin treatment on healthy tissues (notably the heart, liver, and kidneys) [69].…”
Section: Current Progress In Glucose Conjugation As An Anticancer mentioning
confidence: 99%
“…This adriamycin glycoconjugate was designed to enhance the selectivity of adriamycin to cancer cells, and thus to counteract the dose-limiting toxicity of adriamycin treatment on healthy tissues (notably the heart, liver, and kidneys) [69]. In cell culture, 2-amino-2-deoxyglucose-conjugated adriamycin was found to have similar potency to its aglycone adriamycin against immortalized cancer cell lines, but the while adriamycin showed substantial toxicity to human embryonic lung fibroblast (HELF) cells at low nanomolar concentrations after 48 hours, 2-amino-2-deoxyglucose-conjugated adriamycin was not toxic to HELF cells at up to 50 nM for 48 hours [69], though the toxicity of higher concentrations of the glycoconjugate were not tested. The intrinsic fluorescence of adriamycin was used to monitor the uptake of 2-amino-2-deoxyglucose-conjugated adriamycin in cells by confocal microscopy.…”
Section: Current Progress In Glucose Conjugation As An Anticancer mentioning
confidence: 99%